2006
DOI: 10.1136/bjo.2005.089219
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell markers: ABCG2 and MCM2 expression in retinoblastoma

Abstract: Backgound/aim: The authors studied the expression of cancer stem cell surface marker, ABCG2, and neural stem cell marker, MCM2, in retinoblastoma and correlated clinicopathologically. Methods: Among 39 retinoblastomas, 18 tumours were not subjected to preoperative/postoperative chemotherapy, 15 tumours underwent postoperative chemotherapy, and six tumours had preoperative chemotherapy. There were 20 tumours with no invasion and 19 tumours with invasion of choroid/optic nerve. ABCG2 and MCM2 expression was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 11 publications
0
38
1
Order By: Relevance
“…16,[38][39][40][41] In addition, immunohistochemical examination on RB pathological specimens demonstrated that RBs exhibited phenotypic heterogeneity, being composed of cells expressing both undifferentiated and differentiated markers. [10][11][12][13][14][15]20,[42][43][44] Hence, these investigators inferred that RB might come from multipotent or bipotent retinal cells. In the present study, we established a link between normal retinal genesis and tumorigenesis of RB with the application of principles for study of normal neural or retinal stem cells to RB tumor cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…16,[38][39][40][41] In addition, immunohistochemical examination on RB pathological specimens demonstrated that RBs exhibited phenotypic heterogeneity, being composed of cells expressing both undifferentiated and differentiated markers. [10][11][12][13][14][15]20,[42][43][44] Hence, these investigators inferred that RB might come from multipotent or bipotent retinal cells. In the present study, we established a link between normal retinal genesis and tumorigenesis of RB with the application of principles for study of normal neural or retinal stem cells to RB tumor cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] As shown in other studies, CD90, a differentiated retinal cell marker, is positive in IRB-1 cells. [31][32][33][34] Neurosphere in RB cells is an indicator of self-renewal and cycling in the stem cells, especially Y79 and WERI-Rb1. 35 IRB-1 showed the capacity to form neurospheres, an indicator of stem cell self-renewal.…”
Section: Chromosome Studiesmentioning
confidence: 99%
“…11 More recent study demonstrated that retinoblastoma cells were positively stained with cancer stem cell surface markers such as ABCG2 and MCM2, supporting that retinoblastoma is derived from stem cells. 12 Other investigators have suggested that the retinoblastoma cells have the same origin as the photoreceptor cells. [13][14][15][16] In contrast to the controversy over the cell origin of retinoblastomas, it has become generally accepted that several types of cancers of the central nervous system arise from the tumour stem cells, 17 which are derived from the transformation of the neural stem cells, and are thought to have self-replication ability and differentiation potency.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has also been suggested that primitive neuroectodermal cells with their potential for both neural and glial cell lineage are the cell origin of retinoblastomas. [8][9][10][11][12] Additionally, when cells from retinoblastoma cultures were investigated with a scanning electron microscope, glial, and neuronal cells were observed, suggesting the cell origin of the retinoblastoma is a multipotential retinal stem cell. 11 More recent study demonstrated that retinoblastoma cells were positively stained with cancer stem cell surface markers such as ABCG2 and MCM2, supporting that retinoblastoma is derived from stem cells.…”
Section: Introductionmentioning
confidence: 99%